Titanium dioxide nanoparticles provide protection against polycyclic aromatic hydrocarbon BaP and chrysene‐induced perturbation of DNA repair machinery: A computational biology approach. (31st December 2015) - Dhasmana, Anupam; Jamal, Qazi Mohd. Sajid; Gupta, Richa; Siddiqui, Mohd. Haris; Kesari, Kavindra Kumar; Wadhwa, Gulshan; khan, Saif; Haque, Shafiul; Lohani, Mohtashim
Abstract: We examined the interaction of polycyclic hydrocarbons (PAHs) like benzo‐α‐pyrene (BaP), chrysene, and their metabolites 7, 8‐dihydro‐7, 8‐dihydroxybenzo(a)pyrene, 9, 10‐oxide (BPDE) and chrysene 1, 2‐diol‐3, 4‐epoxide‐2 (CDE), with the enzymes involved in DNA repair. We investigated interaction of 120 enzymes with PAHs and screened out 40 probable targets among DNA repair enzymes, on the basis of higher binding energy than positive control. Out of which, 20 enzymes lose their function in the presence of BaP, chrysene, and their metabolites, which may fetter DNA repair pathways resulting in damage accumulation and finally leading to cancer formation. We propose the use of nanoparticles as a guardian against the PAH's induced toxicity. PAHs enter the cell via aryl hydrocarbon receptor (AHR). TiO2 NP showed a much higher docking score with AHR (12, 074) as compared with BaP and chrysene with AHR (4, 600 and 4, 186, respectively), indicating a preferential binding of TiO2 NP with the AHR. Further, docking of BaP and chrysene with the TiO2 NP bound AHR complex revealed their strong adsorption on TiO2 NP itself, and not on their original binding site (at AHR). TiO2 NPs thereby prevent the entry of PAHs into the cell via AHR and hence protect cells against the deleterious effects induced by PAHs.